An Overview: The Corporate Social Responsibility on Employee Attitudes and Behaviors - Al Halbusi, H. (Academy of Management, 2017)
This paper amis to give an overview on the subject of the corporate social responsibility on employee attitudes and behaviours (CSR) in the recent years, it can be noticed that different scholars were still continue to look at the concept of CSR in different perspectives. In 1970, where Milton Friedman decided to write an article where he provoke by disputing the responsibilities of corporations. After that academicians start to look at the concept of CSR in more details, and made a move from the debating room where they were mainly discussing about the legitimacy of CSR to the room of understanding it more. But, most of the researches which have been conducted with regard to CSR they were mainly focusing on macro perspective, where you will be able to find most of the scholars were focusing on the relationship that exists between CSR initiatives and financial performance.